2022
DOI: 10.1155/2022/5777946
|View full text |Cite
|
Sign up to set email alerts
|

A Signature for Smoking Status of Coronary Heart Disease Patients through Weighted Gene Coexpression Network Analysis

Abstract: Background. Smoking is one of the risk factors of coronary heart disease (CHD), while its underlying mechanism is less well defined. Purpose. To identify and testify 6 key genes of CHD related to smoking through weighted gene coexpression network analysis (WGCNA), protein-protein interaction (PPI) network analysis, and pathway analysis. Methods. CHD patients’ samples were first downloaded from Gene Expression Omnibus (GEO). Then, genes of interest were obtained after analysis of variance (ANOVA). Thereafter, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…From the results of the statistical analysis, it is observed that the vast majority of patients with coronary heart disease have smoked in the past and continue to smoke, despite knowing that smoking is very harmful to health and the doctor's advice to stop smoking immediately. This is in favor of the relationship between smoking and coronary heart disease that has been reported in previous studies (Shang et al, 2022;Salehi et al, 2021;Banks et al, 2019;Stallones, 2015;Tolstrup et al, 2014;Baba et al, 2006;He & Lam, 1999;Rigotti & Pasternak, 1996).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…From the results of the statistical analysis, it is observed that the vast majority of patients with coronary heart disease have smoked in the past and continue to smoke, despite knowing that smoking is very harmful to health and the doctor's advice to stop smoking immediately. This is in favor of the relationship between smoking and coronary heart disease that has been reported in previous studies (Shang et al, 2022;Salehi et al, 2021;Banks et al, 2019;Stallones, 2015;Tolstrup et al, 2014;Baba et al, 2006;He & Lam, 1999;Rigotti & Pasternak, 1996).…”
Section: Discussionmentioning
confidence: 59%
“…Cardiovascular disease refers to a set of disorders of the heart and blood vessels and includes, among others, coronary artery disease (Appleton & Kubzansky, 2014). Smoking has been associated with morbidity and mortality from coronary heart disease for several decades (Shang et al, 2022;Salehi et al, 2021;Banks et al, 2019;Stallones, 2015;Tolstrup et al, 2014;Baba et al, 2006;He & Lam, 1999;Rigotti & Pasternak, 1996).…”
Section: Introductionmentioning
confidence: 99%